Perbedaan Daya Makan Ikan Wader Pari (Rasbora argyrotaenia), Ikan Wader Bintik Dua (Puntius binotatus), dan Ikan Kepala Timah (Aplocheilus panchax) sebagai Predator Jentik Nyamuk Aedes sp - Muhammad Andy Firmansyah; Indah Werdiningsih; Purwanto Purwanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2015)
Dengue Haemorrhagic Fever is still one of health problems in Indonesia. The transmission of thedisease is by the bites of it’s vector insect i.e. Aedes sp. Therefore, the population of this mosquito must be controlled, one of which is by using larvae-eating fishes. The purpose of the study was to know the difference in ability of three fish species, namely: Aplocheilus panchax, Rasbora argerotaenia and Puntius binotatus, as predator of the mosquito larvae, by conducting a preexperiment study with pre-test and post-test design. From ten replications, it was identified that Aplocheilus panchax fish ate the Aedes sp larvae more than the other two species did. The predation ability of this species was 34 larvaes for 10 minutes in average, meanwhile the two latterfishes were of 27 and 21 larvaes. Based on the one way anava statistical test at 95 % confidence level, the corresponding p-value was obtained < 0,001, which means that the above differences were significant. So that, it is suggested for the community to benefitted Aplocheilus panchax in the eradicating of Aedes sp.